Dexmedetomidine postconditioning attenuates myocardial ischemia/reperfusion injury by activating the Nrf2/Sirt3/SOD2 signaling pathway in the rats. (31st December 2023) - Hu, Bin; Tian, Tian; Li, Xin-Tao; Hao, Pei-Pei; Liu, Wei-Chao; Chen, Ying-Gui; Jiang, Tian-Yu; Chen, Pei-Shan; Cheng, Yi; Xue, Fu-Shan
ABSTRACT: Objectives: To observe the protective effects of dexmedetomidine (Dex) postconditioning on myocardial ischemia/reperfusion injury (IRI) and to explore its potential molecular mechanisms. Methods: One-hundred forty-seven male Sprague-Dawley rats were randomly divided into five groups receiving the different treatments: Sham, ischemia/reperfusion (I/R), Dex, Brusatol, Dex + Brusatol. By the in vivo rat model of myocardial IRI, cardioprotective effects of Dex postconditioning were evaluated by assessing serum CK-MB and cTnI levels, myocardial HE and Tunel staining and infarct size. Furthermore, the oxidative stress-related markers including intracellular ROS level, myocardial tissue MDA level, SOD and GSH-PX activities were determined. Results: Dex postconditioning significantly alleviated myocardial IRI, decreased intracellular ROS and myocardial tissue MDA level, increased SOD and GSH-PX activities. Dex postconditioning significantly up-regulated myocardial expression of Bcl-2, down-regulated Bax and cleaved caspase-3 and decreased cardiomyocyte apoptosis rate. furthermores, Dex postconditioning promoted Nrf2 nuclear translocation, increased myocardial expression of Sirt3 and SOD2 and decreased Ac-SOD2. However, brusatol reversed cardioprotective benefits of Dex postconditioning, significantly decreased Dex-induced Nrf2 nuclear translocation and reduced myocardial expression of Sirt3 and SOD2. Conclusions: Dex postconditioning can alleviate myocardial IRI by suppressing oxidative stress and apoptosis, and these beneficial effects are at least partly mediated by activating the Nrf2/Sirt3/SOD2 signaling pathway.